Modeling of cell growth and phoA-directed expression of cloned genes in recombinant Escherichia coli - Shin, P.K.; Koo, J.H.; Lee, W.J.; Seo, J.H. (Korean Institute of Chemical Engineers, 1996)
A mathematical model was formulated to describe growth and cloned protein production in the recombinant Escherichia coli cells containing phoA-directed expression systems. Kinetic parameters for the strains with two fusion genes (phoA-lacZ either on the chromosome or on a multicopy plasmid and phoA-amyE on a multicopy plasmid) were estimated and compared to analyze the effects of cloning site (chromosome and plasmid), product type (E. coli β-galactosidase and Bacillus subtilis α-amylase), and culture temperature on the cell's behavior. The presence of a multicopy plasmid reduced the specific growth rate and the phosphate uptake rate of the cell, both by 10%, compared with those of the chromosome-integrated strain. The overexpression of B. subtilis α-amylase decreased the specific growth rate and the glucose consumption rate more than the β-galactosidase overproduction system. The presence of multiple copies of the phoA promoter on either an intact phoA gene or the fusion gene reduced both the repression and derepression efficiencies. Culture temperatures showed a significant effect on α-amylase production. A temperature of 30°C is more desirable than 37° for α-amylase production in the recombinant E. coli containing the phoA promoter.